Pengaruh Struktur Modal Dan Likuiditas Terhadap Nilai Perusahaan Dengan Profitabilitas Sebagai Variabel Intervening Pada Perusahaan Manufaktur Sub Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Periode 2020-2024 - Aulia Darmaya Putri (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to examine the effect of capital structure and liquidity on firm value with profitability as an intervening variable in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2020-2024. The sampling technique used purposive sampling with a total of 28 companies and 140 observations. Data analysis techniques used multiple linear regression analysis and path analysis with SPSS 26. The results showed that simultaneously (F-test) capital structure and liquidity have a significant effect on profitability with F count 8.918 > F table 3.062 (sig. 0.000), likewise capital structure, liquidity, and profitability have a simultaneous significant effect on firm value with F count 31.131 > F table 2.671 (sig. 0.000). Partially (t-test), capital structure has a negative and significant effect on profitability (t = -3.180; sig. 0.002), while liquidity does not have a significant effect on profitability (t = -0.930; sig. 0.354). Capital structure has a positive and significant effect on firm value (t = 2.578; sig. 0.011), while liquidity does not affect firm value (t = -0.053; sig. 0.958). Profitability has a positive and significant effect on firm value (t = 9.549; sig. 0.000). Adjusted R² value for equation 1 is 0.102 (10.2%) and equation 2 is 0.394 (39.4%). The mediation analysis results show that profitability cannot mediate the effect of capital structure on firm value (direct effect 0.299 > indirect effect 0.003), but profitability can mediate the effect of liquidity on firm value (indirect effect 0.001 > direct effect -0.006). This research provides practical implications for company management to optimize capital structure and increase profitability to maximize firm value.